Medieval India : from Sultanat to the Mughals - Bhargava, Meena (New Delhi : Orient BlackSwan, 2010)
Contributed articles.
v. 1. Politics, economy, religion -- v. 2. Culture, gender, regional patterns.
Includes bibliographical references.
Keywords: India -- History -- 1526-1765.